Implantable Antennas for Biomedical Purposes: State-of-the-Art, Challenges, and Future Directions - Amri, Muhammad Miftahul; Hisan, Urfa Khairatun; Sulisworo, Dwi (Indonesian Review of Physics, 2024)
This article provides a comprehensive review of implantable antennas in the context of their application within the biomedical field. Through a systematic exploration of cutting-edge developments and associated challenges, a thorough understanding of antenna design, performance considerations, and safety implications is obtained. The investigation thoroughly examines diverse antenna types, including planar, microstrip, fractal-geometry, and others, elucidating the design considerations that govern their suitability for a wide array of implantable medical devices (IMDs). Substrate and material choices are critical factors influencing antenna efficiency and biocompatibility. The utilization of available frequency bands is evaluated, highlighting the inherent tradeoffs that dictate their applicability in biomedical applications. Additionally, the promising domain of rectenna technology is explored for its potential in sustainable energy harvesting. The discourse on miniaturization techniques underscores their pivotal role in enabling the seamless integration of antennas within intricate implant structures. Safety aspects are paramount, encompassing metrics such as specific absorption range (SAR), maximum permissible exposure (MPE) limits, and thresholds for localized temperature changes. The intricate interplay between human body effects and antenna performance is briefly elaborated. Methodologies for thorough evaluation, spanning computer simulations, as well as experiments in in vivo and in vitro scenarios, are discussed for their pivotal role in iteratively refining antenna functionality.